2006
DOI: 10.1007/s11277-006-9127-5
|View full text |Cite
|
Sign up to set email alerts
|

W-CDMA Uplink Practical Capacity and Interference Statistics of Rural Highways Cigar-Shaped Microcells with Imperfect Power Control and Finite Transmitted Power

Abstract: The capacity and the interference statistics of the sectors of the cigar-shaped W-CDMA microcell are studied. A model of 5 microcells is used to analyze the uplink. The microcells are assumed to exist in rural zones. The capacity and the interference statistics of the microcell are studied for different sector range, different antenna side lobe levels, different values of the break point distance, different values of the propagation parameter s 2 and different standard deviation of the power control error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…It has been shown that in this scenario the capacity is minimum when trains are in the midway between the base stations. In [9], the W-CDMA uplink practical capacity and interference statistics of rural highways cigar-shaped microcells with imperfect power control and finite transmitted power have been given where the two-slope model of propagation has been used to calculate the propagation loss. In [10], the WCDMA multiservice (voice and data) uplink capacity of highways cigar-shaped microcells has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in this scenario the capacity is minimum when trains are in the midway between the base stations. In [9], the W-CDMA uplink practical capacity and interference statistics of rural highways cigar-shaped microcells with imperfect power control and finite transmitted power have been given where the two-slope model of propagation has been used to calculate the propagation loss. In [10], the WCDMA multiservice (voice and data) uplink capacity of highways cigar-shaped microcells has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], Taha-Ahmed et al studied the capacity and statistics of the cigar-shaped highways microcells without giving the intracellular interference variance assuming perfect power control and infinite transmitted power. In [9], the WCDMA uplink practical capacity and interference statistics of rural highways cigar-shaped microcells has been given assuming imperfect power control and finite transmitted power where only one service at a given time has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the W-CDMA uplink capacity and interference statistics of cigar-shaped microcells in over-ground train service with imperfect power control was studied assuming unlimited transmitted power and ignoring the power assigned to the W-CDMA uplink pilot. In [7], the W-CDMA uplink capacity and interference statistics of rural highways cigar-shaped microcells with imperfect power control and uniform distribution of users were obtained. In [8] which represent one of the newest works in this area, the WCDMA multiservice uplink capacity of highways cigar-shaped microcells has been given assuming simultaneous voice and data services.…”
mentioning
confidence: 99%
“…The entire up mentioned works except [5] and [6] have assumed uniform distribution of users within the microcells (up to 100 simulation points in each sector). No one of the above mentioned works except [3] has taken into account the effect of the multipath components that can exist due to the nearer scatterers.…”
mentioning
confidence: 99%